Persistent growth of anthropogenic non-methane volatile organic compound (NMVOC) emissions in China during 1990–2017: drivers, speciation and ozone formation potential - Li, Meng; Zhang, Qiang; Zheng, Bo; Tong, Dan; Lei, Yu; Liu, Fei; Hong, Chaopeng; Kang, Sicong; Yan, Liu; Zhang, Yuxuan; Bo, Yu; Su, Hang; et al. (Atmospheric chemistry and physics, 2019)
Non-methane volatile organic compounds (NMVOCs) are important ozone and secondary organic aerosol precursors and play important roles in tropospheric chemistry. In this work, we estimated the total and speciated NMVOC emissions from China's anthropogenic sources during 1990–2017 by using a bottom-up emission inventory framework and investigated the main drivers behind the trends. We found that anthropogenic NMVOC emissions in China have been increasing continuously since 1990 due to the dramatic growth in activity rates and absence of effective control measures. We estimated that anthropogenic NMVOC emissions in China increased from 9.76 Tg in 1990 to 28.5 Tg in 2017, mainly driven by the persistent growth from the industry sector and solvent use. Meanwhile, emissions from the residential and transportation sectors declined after 2005, partly offsetting the total emission increase. During 1990–2017, mass-based emissions of alkanes, alkenes, alkynes, aromatics, oxygenated volatile organic compounds (OVOCs) and other species increased by 274 %, 88 %, 4 %, 387 %, 91 % and 231 %, respectively. Following the growth in total NMVOC emissions, the corresponding ozone formation potential (OFP) increased from 38.2 Tg of O3 in 1990 to 99.7 Tg of O3 in 2017. We estimated that aromatics accounted for the largest share (43 %) of the total OFP, followed by alkenes (37 %) and OVOCs (10 %). Growth in China's NMVOC emissions was mainly driven by the transportation sector before 2000, while industry and solvent use dominated the emission growth during 2000–2010. Since 2010, although emissions from the industry sector and solvent use kept growing, strict control measures on transportation and fuel transition in residential stoves have successfully slowed down the increasing trend, especially after the implementation of China's clean air action since 2013. However, compared to large emission decreases in other major air pollutants in China (e.g., SO2, NOx and primary PM) during 2013–2017, the relatively flat trend in NMVOC emissions and OFP revealed the absence of effective control measures, which might have contributed to the increase in ozone during the same period. Given their high contributions to emissions and OFP, tailored control measures for solvent use and industrial sources should be developed, and multi-pollutant control strategies should be designed to mitigate both PM2.5 and ozone pollution simultaneously.